THE STUDENTS’ ATTITUDE AND READING COMPREHENSION TOWARD ENGLISH ACHIEVEMENT - Indah Indrawati; Hasia Marto; Maria Eufrasia Ngoyo (Universitas Madako Tolitoli, 2020)
The objective of this research uses to find out the correlation between students’ attitude and reading comprehension toward English achievement. This research is correlation research. The sample of this research consisted 15 students of XI MIA. The data are obtained from questioner, test and last final result (report). In measuring the data correlation, the researcher used SPSS 21 program. The finding of this research, (1) The result of the students’ attitude toward English achievement was 0,013 > 0,05. It indicates that there is no correlation between students’ attitude toward English achievement. (2) The result of reading comprehension toward English achievement was 0,066 > 0,05. It means that there is no correlation between reading comprehension toward English achievement. (3) The result showed students’ attitude and reading comprehension toward English achievement simultaneously was 0,973>0,05. It can be concluded that there is no correlation between students’ attitude and reading comprehension toward English achievement at the second grade of SMA Katolik Atmajaya Tolitoli.Keywords:Correlation, Attitude, Reading Comprehension, English Achievement.